Competitiveness of the La Libertad region in agricultural exports, Peru, 2011-2023 - Alberto-Marcos Soriano-Colchado; Ramón-Alberto Diez-Matallana; Raquel-Margot Gómez-Oscorima*; Luis-Alberto Jiménez; Carolay-Zully Vasquez-Quispe (Наукові горизонти)
The increasing global demand for high-value agricultural products emphasises the need to understand regional export competitiveness. The study aimed to evaluate La Libertad’s comparative advantages in agricultural exports from 2011 to 2023. By employing the Revealed Comparative Advantage (RCA), Export Comparative Advantage (ECA), and Import Comparative Advantage (ICA) indices, alongside Porter’s Diamond, the region’s performance and the determinants of competitiveness across 11 key export products were analysed. These products include fruits such as blueberries, avocados, and grapes, as well as vegetables such as asparagus and piquillo peppers. The analysis revealed strong ECAs for fruits and vegetables, with values ranging from 1.56 to 7.08, and a promising specialisation in cane sugar (RCA of 1.28). The findings indicate that most of these products possess strong to moderate comparative advantages in international markets, with products like blueberries and avocados leading in competitiveness. However, certain challenges remain, including the need for strategic business management and technological innovation to maintain and improve the sector’s competitiveness. The study underscores the importance of continuous monitoring and adaptation to ensure the sustainability and growth of Peru’s agro-export sector. These findings offer valuable insights for policymakers and regional planners seeking to enhance La Libertad’s agricultural export potential